2020
DOI: 10.20944/preprints202007.0096.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Montmorillonite K10: An Efficient Organo- Heterogeneous Catalyst for Synthesis of Benzimidazole Derivatives

Abstract: The use of alternative synthetic methods, in the face of traditional processes that do not conform to the principles of Green Chemistry, represent a problem in the pharmaceutical industry. The procedures for the synthesis of benzimidazole derivatives have become a focus in synthetic organic chemistry, as they are building blocks of strong interest for the synthesis of compounds with pharmacological activity. Various benzimidazole derivatives have found very strong application in medicine and their synt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…They also observed that catalyst was recycled for five runs without an appreciable loss in its catalytic activity. A simple and eco-friendly montmorillonite K10 (MK10) catalyzed method for the synthesis of benzimidazole derivatives (106) has been developed via one-pot reaction between ophenylenediamine (105) and substituted aldehydes (8) by Bonacci and his coworkers (Scheme 150) 193 .…”
Section: Scheme 19: Ps-gacl3-catalyzed Synthesis Of Substituted Coumarinsmentioning
confidence: 99%
“…They also observed that catalyst was recycled for five runs without an appreciable loss in its catalytic activity. A simple and eco-friendly montmorillonite K10 (MK10) catalyzed method for the synthesis of benzimidazole derivatives (106) has been developed via one-pot reaction between ophenylenediamine (105) and substituted aldehydes (8) by Bonacci and his coworkers (Scheme 150) 193 .…”
Section: Scheme 19: Ps-gacl3-catalyzed Synthesis Of Substituted Coumarinsmentioning
confidence: 99%
“…Recent research on the use of eco-sustainable solvents in organic chemistry for the synthesis of benzimidazoles [60][61][62] has had great prominence in the scientific community as well as the use of Lewis acid catalysis exploitation homogeneous catalysts [63][64][65][66] in mild reaction conditions. At the same time, experimental reactions using solid supports in conventional solvents [67][68][69][70], in green solvents [71,72] or under solvent-free conditions [73][74][75][76] performed and the use of heterogeneous catalyst under solvent-free conditions [77] has been particularly important for the eco-sustainable synthesis of benzimidazoles.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Montmorillonite K10 clay (Mont. K10) has been widely studied and utilized, since it offers a number of advantages, including strong acidity, easy recovery, generally mild reaction conditions, easy work up procedures and results in products in high yields [11–17] . Further, it shows unique properties like cation exchange capacity and swelling ability, thereby accommodating various guest species in its inter layers.…”
Section: Introductionmentioning
confidence: 99%